Littoral compound ascidians (Tunicata) from São Sebastião, Estado de São Paulo, Brazil - Rodrigues, S. A.; Rocha, R. M. (Proc. Biol. soc. Wash., 1993)
Compound ascidians were collected during a two-year survey of intertida1 and shallow subtida1 habitats near São Paulo, BraziI. Among the fourteen species recorded, Distaplia bermudensis and Botryllus giganteum are new to São Sebastião, and Didemnum psammathodes, Trididemnum orbiculatum, and Symplegma rubra are new to South America.